Production and Characterization of a Milk-clotting Protease Produced in Submerged Fermentation by the Thermophilic Fungus Thermomucor indicae-seudaticae N31 - Silva, B. L. [UNESP]; Geraldes, F. M. [UNESP]; Murari, C. S. [UNESP]; Gomes, E. [UNESP]; Da-Silva, R. [UNESP] (Humana Press Inc, 2014)
Proteases are some of the most important industrial enzymes, and one of their main applications is for the production of cheese in the dairy industry. Due to a shortage of animal rennet, microbial coagulant proteases are being sought. In this work, the production of microbial rennet from Thermomucor indicae-seudaticae N31 was studied in submerged fermentation. The best enzyme production was obtained in a fermentation medium containing 4 % wheat bran as the substrate in 0.3 % saline solution, incubated for 72 h at 45 degrees C and 150 rpm. The value of the milk clotting activity (MCA) was 60.5 U/mL, and the ratio to proteolytic activity (MCA/PA) was 510. The crude enzyme showed optimum pH at 5.5 and two peaks of optimum temperature (MCA at 65 degrees C and PA at 60 degrees C). The MCA was stable in the pH range 4.0-4.5 for 24 h and up to 55 degrees C for 1 h. It was stable during storage at different temperatures (-20 to 25 degrees C) for 10 weeks. Based on these results, we conclude that microbial rennet from T. indicae-seudaticae N31 produced by submerged fermentation showed good prospects of replacing traditional rennet.
Keywords: Microbial coagulant; Wheat bran; Thermophilic fungi; Rennet; Fermentation